Molecular Modeling Studies on Biochanin-A as a Potential Dual Inhibitor for VEGFR-2 and Cyclin D1-CDK-4 Complex - Mohamed Mahmoud Ramadan; Amgad Albohy; Suher Kamal Zada; Mai Fathy Tolba; Dalal Abu-ELElla (Ain Shams University, 2021)
Biochanin-A is a known phytoestrogen that is mainly found in red clover. It has several biological activities including anticancer, anti-inflammatory and antioxidant effects. Preclinical studies showed that Biochanin-A has anticancer properties in different cancer models. This effect was found to happen through a diversity of mechanisms inducing cell cycle arrest, apoptosis and antiangiogenic effects. Moreover, despite being a promising nature-derived anticancer agent, there is a paucity of information regarding specific target validation studies for Biochanin-A. In this study we first predicted the physicochemical properties of Biochanin-A using two different online tools (SwissADME and pkCSM), and then we performed an in silico molecular docking studies for Biochanin-A as a potential dual inhibitor for Cyclin-D1-cyclin dependent kinase (CDK) 4 complex and vascular endothelial growth factor receptor (VEGFR-2) which are key molecular targets for cancer therapy. The results suggest that Biochanin-A interacts with both Cyclin D1-CDK4 complex and VEGFR-2 with a docking affinity that is comparable to their standard inhibitors. These results open the door for further follow up investigations.